Understanding spatial and temporal shifts in taxonomic and functional diversity: assessing dung beetles in a human-modified amazonian landscape - Silva, Wallace Beiroz Imbrosio da (2016)
Thesis submitted for the degree of Doctor of Philosophy as a Dual PhD with ‘Ecologia Aplicada’ Postgraduate Program, Universidade Federal de Lavras, Brazil and Lancaster Environment Centre, Lancaster University, United Kingdom.